Biotechnological potential of açaí (Euterpe oleracea Mart.) seeds for biofuel production - Ribeiro, Júlia Antunes Tavares; Gonçalves, Daniel Bonoto (Seven Editora, 2023)
The economic progress associated with the consumption habits of society, in general, has presented increasing generation and accumulation of solid waste. This is because, in most cases, there is no proper reuse of waste in the production process. Given this scenario, the concept of Circular Economy (CE) arises, seeking to transform the linear production model, based on the concept of extract, produce, consume and dispose, into a circular model, in which materials must return to the production cycle (Siqueira & Moraes, 2009). DOI: https://doi.org/10.56238/colleinternhealthscienv1-049